2018
DOI: 10.1007/s12070-018-1298-3
|View full text |Cite
|
Sign up to set email alerts
|

Post Stapedotomy Vestibular Deficit: Is CO2 Laser Better than Conventional Technique? A Non-randomized Controlled Trial

Abstract: The current standard of care for surgical management of Otosclerosis is small fenestra stapedotomy, which can be done by CO Laser assisted as well as conventional techniques. Vertigo is the commonest complication after stapes surgery. The use of CO Laser has been rising recently owing to its no touch principle, high precision and possibly lower risk of vertigo post operatively. To compare the post-operative vestibular deficit in patients of Otosclerosis having undergone small fenestra stapedotomy by convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…After a minimum follow-up of one year, all patients had a DHI-I score showing no subjective vestibular handicap. According to Singh et al [29] who observed an earlier recovery of vestibular function after the CO 2 laser-assisted technique, our findings confirm that the limited inner ear impairment associated with the CO 2 laser is minimal and reversible, supporting the safety of this surgical instrument.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…After a minimum follow-up of one year, all patients had a DHI-I score showing no subjective vestibular handicap. According to Singh et al [29] who observed an earlier recovery of vestibular function after the CO 2 laser-assisted technique, our findings confirm that the limited inner ear impairment associated with the CO 2 laser is minimal and reversible, supporting the safety of this surgical instrument.…”
Section: Discussionsupporting
confidence: 84%
“…However, there are only a few studies that quantify vestibular injury after laser stapedotomy, probably because no correlation was found between audiological results and vestibular sufferance [28], which is therefore underestimated when good hearing outcomes are obtained. Singh and coworkers [29] assessed the post-stapedotomy (manual perforator vs. CO 2 laser) vestibular function by measuring body sway velocity using the modified clinical test of sensory interaction on balance by static posturography; their study demonstrated a significant postoperative vestibular deficit regardless of the technique used. The acute vestibular disorders after stapedotomy can be due to viral or bacterial labyrinthitis, bleeding or irritating bony fragments in the vestibule, a floating footplate, presence of a perilymphatic fistula, or an overlong prosthesis [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures on the footplate (such as a stapedotomy) may well interfere with the ML and so indirectly affect the utricular macula (see also Mukherjee et al, 2019). Such interference could be responsible for some reports of disorientation or postural unsteadiness that some patients experience following stapedotomy or stapedectomy operations (Bartel et al, 2020; Mun et al, 2019; Singh et al, 2018; Vaughan et al, 2020). Importantly, the anterolateral attachment of the ML lies superior to the footplate's long axis, coming in closest proximity to the footplate in its posterior two‐thirds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the advantages and disadvantages of these devices compared with conventional techniques in thyroid surgeries 3,5–21 . Use of harmonic technology has been shown to be associated with numerous advantages over conventional hemostatic techniques, including lower cost, 3 shorter operative times, 5–14,22 less intraoperative blood loss, 14 shorter hospital stay, 8 transient hypocalcemia, 7,9,11 and less postoperative pain 7,8,11 .…”
mentioning
confidence: 99%
“…LigaSure system use was associated with shorter operative times 16–19 and hospital stays 17 . One study, however, demonstrated higher cost with LigaSure use 20 . A review of both randomized and nonrandomized prospective controlled trials reported that LigaSure use was associated with shorter procedure times with similar rates of blood loss, hospital stay, and postoperative complications 21 …”
mentioning
confidence: 99%